The Meaning of Marriage:: A Phenomenological Study of Women Married at Early Age - Massinai, Sitti Muthia Maghfirah (Martabat: Jurnal Perempuan dan Anak, 2020)
Adolescents’ developmental tasks are including associating with peers, looking and building for self-identity, and exploring the environment.  However, the number of marriage case in adolescence keeps increasing, resulting to the adolescents to face the developmental task that usually faced in early adulthood.  This study explores the meaning of marriage for women who are married at
Keywords: Early Marriage; Adolescence; Meaning of Marriage